A Rare Combination of Tetralogy of Fallot and a Complete Atrioventricular Septal Defect: A Case Report - Josephat M. Chinawa; Awoere T. Chinawa; Jude T. Onyia; Chiesonu D. Nzeduba; Nonyelum C. Maduka; Ogonna O. Nwankwo; Samuel Agwu (International Journal of Medicine and Health Development)
Tetralogy of Fallot (TOF) and a complete atrioventricular septal defect—TOF-atrioventricular (AV) canal defect is a very rare complex congenital heart defect. A very high index of suspicion is crucial for making a diagnosis. AYZ is a 7-year-old male who presented with breathlessness, bluish discoloration of the buccal mucosa, and easy tiredness. Examination showed a child in mild respiratory distress, with hyperemic conjunctiva, and saturates at 80% in room air with grade 4 finger clubbing and grade 3 ejection systolic murmur maximal at the second upper inter-space and soft second heart sound. Echocardiography showed a diagnosis of TOF-AV canal defect. The child was commenced on oral propranolol and an anti-failure regimen and is now being worked up for surgery. A very high index of suspicion is key in the early diagnosis and management of this rare complex cardiac anomaly.